The Effect of Mergers and Acquisitions on Firm Performance- Evidence from China - Cai, JunJie (2019)
This dissertation analyzes 457 mergers and acquisitions transactions between Chinese listed companies on the Shanghai and Shenzhen exchanges between 2014 and 2018. This dissertation uses the event research method to investigate the abnormal performance of the acquisition company in the stock market in the short-term after the merger and acquisition event. The abnormal returns are mostly positive, indicating that most companies benefit from mergers and acquisitions, and then further test some with OLS regression analysis. The effect of factors on cumulative abnormal returns. Regression analysis shows that the size of the acquiring company, payment method, ROA, and ROE. all have more or less significant influences on the accumulated abnormal returns under the four event Windows. The results show that the cash payment method is better than the stock payment, and the abnormal returns of the stocks of small companies after merger and acquisition are more obvious. Overall, in the past five years, most Chinese listed companies have obtained short-term abnormal returns from mergers and acquisitions.